2006
DOI: 10.1086/505496
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS: Management of Herpes Simplex Virus Type 2 Infection in HIV Type 1–Infected Persons

Abstract: Human immunodeficiency virus type 1 (HIV-1)-infected persons have high rates of herpes simplex virus type 2 (HSV-2) infection, ranging from 50% to 90% in studies of HIV-infected populations from different parts of the world. Genital herpes in persons with HIV type 1 (HIV-1) infection is associated with more-severe and chronic lesions, as well as increased rates of asymptomatic genital shedding of HSV-2. Nucleoside analogues (acyclovir, valacyclovir, and famciclovir) decrease the frequency and severity of HSV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 123 publications
0
97
0
3
Order By: Relevance
“…Suppression of HSV coinfection may provide a novel therapeutic strategy for achieving this goal. Indeed, some authors (76,77) have already suggested that all HSV-2-HIVcoinfected individuals receive chronic anti-HSV therapy with acyclovir or its prodrugs for this purpose, but clinical trial data in support of this recommendation are currently lacking. HSV-2 therapy may also be of benefit to individuals already using HAART, in whom adjunctive measures to improve the effectiveness of antiretroviral therapy are still needed.…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%
“…Suppression of HSV coinfection may provide a novel therapeutic strategy for achieving this goal. Indeed, some authors (76,77) have already suggested that all HSV-2-HIVcoinfected individuals receive chronic anti-HSV therapy with acyclovir or its prodrugs for this purpose, but clinical trial data in support of this recommendation are currently lacking. HSV-2 therapy may also be of benefit to individuals already using HAART, in whom adjunctive measures to improve the effectiveness of antiretroviral therapy are still needed.…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%
“…Of the substances tested, galangin and kaempferol (Fig. 4) had the highest anti-HSV activity, reducing the viral titer by 2log 10 or more (38). This was confirmed by Lyu et al, who additionally demonstrated that the two substances had high anti-HSV in vitro activity, and that flavonols had higher activity than flavones (39).…”
Section: Natural Products With Anti-herpes Simplex Virus Activitymentioning
confidence: 57%
“…Nonetheless, in recent years the incidence of genital herpes caused by HSV-1 has increased significantly in some developed countries (7), probably because a decreased likelihood of contracting HSV-1 infection during early childhood has led to increased chances of infection during sexual contact. This is particularly worrisome as genital herpes infections have been shown to at least double the risk of sexually-acquired HIV infections (5,8,9), with the prevalence of HSV-2 in HIV-infected individuals estimated to be as high as 90% in certain populations (10).…”
Section: Standard Treatment Of Herpes Simplex Virus Infectionsmentioning
confidence: 99%
“…Similar to immunocompetent individuals, reactivation is subclinical in most cases [57]. However, the form of reactivation is closely related with the rate of immunosuppression and ulcerate, necrotic, painful, massive, multiple, and atypical lesions may be observed especially in patients with Fundamentals of Sexually Transmitted Infectionslow CD4+ cell count [58]. Resistance is a high possibility in HIV+ patients.…”
Section: Hsv Management In Hiv-positive Patientsmentioning
confidence: 99%